Reproductive performance of cows after fixed‐time artificial insemination with ovulation synchronisation and re‐synchrony in southern Australian dairy herds. Issue 4 (25th March 2018) - Izzo, MM; Humphris, M; Pryor, L; Perry, A; Morton, JM
Abstract : Objective: To describe reproductive performance of lactating dairy cows after fixed‐time artificial insemination (FTAI) with ovulation synchronisation and re‐synchrony in Australian dairy herds, and to compare reproductive outcomes with those of conventional mating programs. Methods: The study was conducted in two seasonally calving dairy herds in which lactating dairy cows (n = 675) were enrolled into three treatment groups: group 1, oestrus detection and AI for 34 days followed by a natural service period; group 2, FTAI on day 1 followed by re‐synchrony of all cows prior to ultrasound pregnancy diagnosis at day 31 and FTAI of cows diagnosed not pregnant at day 34, then a natural service period; group 3, FTAI on day 1 followed by oestrus detection and AI for 34 days, then a natural service period. First‐service conception rate (FSCR), 6‐week in‐calf (6WIC) rate and proportions pregnant at the end of mating were compared using logistic regression with farm fitted as a fixed effect. Times from mating start date to conception were described using survival analysis with Kaplan‐Meier failure functions. Results: FSCRs (45.3%, 49.1% and 45.6% for groups 1, 2 and 3, respectively) and proportions pregnant at the end of mating (77.6%, 76.0% and 76.8% for groups 1, 2 and 3, respectively) were similar for all groups. The 6WIC rate in group 2 was similar to that in group 3 (70.4% vs. 67.2%; P = 0.486), but tended to be higher than in group 1 (70.4% vs. 62.0%, P = 0.066). The median days to pregnancy for cows that conceived was 1 day in groups 2 and 3 and 10 days in group 1. Conclusion: Mating plans that use FTAI with ovulation synchronisation and re‐synchrony during the AI period can achieve comparable reproductive performance to conventional mating programs in seasonally calving dairy herds.